Pastors and pluralism in Württemberg, 1918-1933 - Diephouse, David J., 1947- (Princeton legacy library., 1987)
Moving beyond earlier explanations of why the Protestant church opposed the Weimar Republic, David Diephouse emphasizes the social role of the church rather than its direct political activity. Originally published in 1987. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.